Systematic Analyses of the Differentially Expressed Alternative Splicing Events in Gastric Cancer and Its Clinical Significance - Lin, Changwei; Yu, Bowen; Zhang, Mao; Chen, Yifei; Li, Liang; Zhao, Deze (Frontiers in Genetics, 2020)
Accumulation of evidence has indicated a close relationship between alternative splicing (AS) and gastric cancer (GC), whereas systematic analyses of the differentially expressed AS events (DEAS) between GC and normal tissues are lacking. RNA-Seq data and the corresponding clinical information were downloaded from TCGA GC cohort. The percent spliced-in (PSI) value calculated in the GC tissues and normal tissues was employed to quantify the DEAS. Further, survival-associated DEAS and DEAS signatures were identified by univariate and multivariate cox regression analyses. To evaluate the association between DEAS and patients' clinical features, Kaplan-Meier analysis, receiver operator characteristic (ROC) curve, Cox proportional regression and nomograms incorporating the DEAS signatures were performed. DEAS and their splicing networks were finally analyzed by bioinformatics methods. In addition, we use the method of random grouping to divide the samples into the training group and the test group. The final results of the two groups are consistent. After strict ﬁltering, a total of 44,935 AS events were identiﬁed, among which 11,141 DEAS were preliminarily screened from 5032 genes. A total of 454 DEAS was associated with OS, and 872 DEAS were associated with DFS. The ﬁnal prognostic signatures were constructed from the survival-associated DEAS with an area under the receiver operating characteristic (ROC) curve (AUC) greater than 0.6. Only ES in ABI1 was simultaneously associated with OS and DFS. Finally, we identified the splicing correlation network between the prognostic splicing factors (SF) and DEAS in GC. Our study provided a systematic portrait of survival-associated DEAS in GC and uncovered splicing networks that are valuable in deciphering the underlying mechanisms of AS in GC.